(untitled) (Revista de Artes Marciales Asiáticas, 2012)
In 1550 d.C. China’s splendor during the Ming Dynasty was threatened by hostiles forces in the northern border as well as its eastern coasts. The appearance of Qi Jiguang, one of the most famous Chinese generals would change the way China trained its military leading to the creation of its first professional army. The following article will discuss the contributions of General Qi Jiguang and his legacy, which is carried on by one of the most powerful armies in the world, The People’s Liberation Army.